Rebel talent why it pays to break the rules at work and in life - Gino, Francesca (Pan Books, 2019)
A behavioral scientist explores why "rebels" with unconventional outlooks who break the rules find the greatest success, discussing how they drive innovation and reinvention by defying the status quo